Sutiyah Heni THE EFFECT OF MOTIVATION AND SKILLS OF PMR IN PROVIDING FIRST AID FOR FAINTING AT AHMAD YANI GURAH VOCATIONAL SCHOOL: THE EFFECT OF MOTIVATION AND SKILLS OF PMR IN PROVIDING FIRST AID FOR FAINTING AT AHMAD YANI GURAH VOCATIONAL SCHOOL - heni, heni (Journal of health research and technology, 2026)
A person's motivation to engage in an activity is influenced by several factors, including intrinsic and extrinsic factors. The motivation of PMR members to participate in PMR training activities in providing first aid to victims of fainting is a drive that arises within students to act or undertake something to achieve their desired goals, one of which is physical fitness. Improving the abilities/skills of PMR members in handling fainting is very important to minimize the risk of secondary injury, speed up the victim's recovery, and save someone's life. To determine the influence of motivation and skills of PMR in providing first aid for fainting at SMK Ahmad Yani Gurah. The research design is descriptive, population and sample of 39 respondents, with total sampling technique. The research was conducted from March 27 to April 30, 2025, variable x is Motivation and variable y is PMR's skill in providing first aid for fainting, instruments with interviews, questionnaires and data observations were analyzed with percentages, and interpreted quantitatively using the ANOVAa Statistical Test with Simple Linear Regression. Most respondents have strong motivation 33 (85%) and a small number of respondents have moderate motivation 6 (15%) and almost all respondents have good skills 33 (85%) and a small number of respondents have sufficient skills 6 (15%), the results of the ANOVA statistical test show an influence in providing first aid for fainting on motivation (p = 0.003) and skills (p = 0.003). This study shows that providing first aid for fainting is influenced by the motivation and skills of the PMR members of SMK Ahmad Yani Gurah. It is hoped that PMR members will be able to improve their motivation and skills related to first aid for fainting, in accordance with their own motivation and skills for others. Keywords: Motivation, Skills, First Aid for Fainting